Clinical and histopathological features of lentigo maligna and lentigo maligna melanoma: a retrospective analysis in Korea - Park, Chanyong; Kim, Dong Hyo; Hur, Keunyoung; Mun, Je-Ho (Frontiers in Medicine, 2024)
Introduction: Lentigo maligna (LM) and Lentigo maligna melanoma (LMM) are rare in Asian countries. The histopathological diagnosis of LM is often challenging, and misdiagnosis is common. Although histopathologic features of LM/LMM are known, statistical analysis of them were scarcely reported. In this study, we aimed to investigate the histopathological characteristics of LM/LMM in Korean patients and identify key histopathological clues distinguishing LM from benign lentigo. Methods: We performed a retrospective study of the clinical and histopathological features of patients diagnosed with LM/LMM at our center between 2011 and 2022. We assessed the histopathological features in each case based on 16 pathological criteria according to previous literature. Pathologically confirmed cases of benign lentigo were analyzed for comparison. Results: Twenty-one patients (10 with LM and 11 with LMM) were analyzed. Several statistically significant difference existed between the features of LM and benign lentigo (N=10), including asymmetry of overall structure (P<0.001), cytologic atypia (P<0.001), predominant single-cell proliferation (P<0.001), melanocytic nests (P=0.033), melanocytes forming rows (P=0.003), pagetoid spread of melanocytes (P<0.001), and hair follicle invasion by atypical melanocytes (P<0.001). Degree of solar elastosis was more severe in group ‘Age≥60’ (P=0.015), and group ‘Diameter≥20 mm' (P=0.043). Presence of elongated rete ridges were less common in the older than 60 age group (P=0.015) and group ‘Diameter≥20 mm'. Invasion was associated with mitosis (P=0.001, OR 49.285), multinucleated cells (P=0.035, OR 17.769), and degree of lymphocyte infiltration (P=0.004). Conclusions: This study investigated the clinical and histopathologic characteristics of LM and LMM in Koreans. Although histopathological diagnosis is challenging, especially in the early stages of LM, our data showed essential histopathological changes in architectural, cytological, and dermal patterns. Considering the potential aggressiveness of LM/LMM, it is essential to recognize its histopathological features and provide timely management.